Implementasi Metode Association Rule Mining Pada Penjualan Barang Di Toko Bangunan Ada Mas Menggunakan Algoritma Apriori - Anton Saputra; Herlina Latipa Sari; Devi Sartika (Universitas Dehasen Bengkulu, 2023)
The purpose of this research is to implement the association rule mining method on sales transaction data at the store and also to find out the most popular and most sold building materials at the Ada Mas Building Shop. The implementation of the Association Rule Mining Method on the sale of goods at the Ada Mas Building Shop is used to provide information on the results of the sales pattern of building materials every month which can be used as a parameter in managing the inventory of building materials at the Ada Mas Building Shop, besides that it can provide information on the most popular and most sold building materials at the Ada Mas Building Shop. Based on sales transaction data for September 2022 as many as 193 transactions, the results of 2 itemset sales patterns using the Association Rule Mining Method that meet the minimum support of 10% and minimum confidence of 50% are the most popular items, namely Iron 10 KSTY, Iron 8 KSTY, and Iron 6 KSTY.